Resilient architecture for cyber-physical production systems - Tomiyama, Tetsuo; Moyen, Florian (Elsevier, 2018)
Production systems are a typical example of cyber-physical systems (CPS) in which a variety of machines, actuators, sensors and control systems are interwoven to produce products as efficiently as possible. Even though sophisticated condition monitoring systems are deployed, stoppage, breaks, and other types of failures still happen. To avoid catastrophic operational disruptions, desirably the production system itself resiliently and autonomously responses to failures. This paper reports a design method for a resilient architecture of a cyber-physical production system that can deal with disturbances and failures in a discrete-event process. A physical demonstrator was built to demonstrate its reconfiguration capabilities.
Keywords: Systems architecture; Reconfiguration; Maintenance